On the Potential Function of Type II Arabinogalactan O-Glycosylation in Regulating the Fate of Plant Secretory Proteins - Seifert, Georg J. (Frontiers in Plant Science, 2020)
Hydroxyproline rich glycoproteins are a plant-specific superfamily of secreted proteins. The highly diverse sub-family of arabinogalactan proteins is implicated with a multitude of biological functions, however, the mechanistic role of O-glycosylation on arabinogalactan proteins is largely elusive. Some models suggest that the O-glycans of arabinogalactan proteins directly function in ligand-receptor interactions, as calcium store or as oligosaccharide signals. Moreover, recent evidence suggests roles for arabinogalactan protein O-glycans in protein trafficking and for protein lifetime. Various types of protein O-glycosylation exist in animal and yeast models where glycans were suggested to determine the fate of glycoproteins by affecting intracellular sorting or proteolytic activation and degradation. In conclusion, O-glycosylation might act as a molecular determinant for cellular localization and protein lifetime of many endogenous proteins, in parallel to additional functions in the apoplast.